2020
DOI: 10.3390/min10020129
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microstructural Analysis and X-ray Computed Tomography of Ores and Rocks—Comparison of Results

Abstract: Profound knowledge of the structure and texture of rocks and ores as well as the behavior of the materials under external loads is essential to further improvements in size reduction processes, particularly in terms of liberation size. New analytical methods such as computer tomography (CT) were adopted to improve the understanding of material characteristics in rocks and ores relevant to mineral processing, particular the crushing and grinding and the modelling/simulation thereof. Results obtained on the text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…When analyzing the The results of the research of these parameters are presented in Table 5. The porosity factor often determines the rock strength characteristics and its behavior during disintegration since the destruction occurs along the weakest zones-the boundaries of individual mineral phases intergrowths, fractures [40][41][42]. When analyzing the pore space characteristics of the samples, it was revealed that the samples have a sufficiently low porosity, which indicates the high strength of the rock itself.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the The results of the research of these parameters are presented in Table 5. The porosity factor often determines the rock strength characteristics and its behavior during disintegration since the destruction occurs along the weakest zones-the boundaries of individual mineral phases intergrowths, fractures [40][41][42]. When analyzing the pore space characteristics of the samples, it was revealed that the samples have a sufficiently low porosity, which indicates the high strength of the rock itself.…”
Section: Resultsmentioning
confidence: 99%
“…The list of analyzed granite samples and extracted zircons, indicating the methods used and the corresponding number of measurements: OM-optical microscopy of granites in thin sections and extracted zircon grains, SEM-scanning electron microscopy (JSM-6460LV, Saint Petersburg, Russia) includes BSE imaging, WDX analysis of zircon and neighboring minerals in thin sections; SEM *-scanning electron microscopy (JEOL JSM-7001F, Freiberg, Germany) includes SE imaging of extracted zircon grains, applied to electrically conductive tape, to study the surface of crystal faces and BSE imaging of zircon grains, impregnated into epoxy resin and polished, to study the inner structure; SIMS-secondary ion mass spectrometry (Cameca IMS-4f, Yaroslavl, Russia) of zircon grains, impregnated into epoxy resin, to measure the trace element content (accompanied with BSE and cathodoluminescence (CL) imaging of zircon inner structure); Raman spectroscopy was applied to measure the degree of zircon crystallinity (Renishaw InVia Raman spectrometer, Saint Petersburg, Russia); XRF analysis of granite samples to determine the content of petrogenic elements and ICP-MS analysis for the petrogenic elements, as well as for a wide range of trace elements (Actlabs, Ancaster, ON, Canada). The analysis of the trace elements content in zircon (67 analytical points/41 grains) was carried out on the Cameca IMS-4f ion microprobe (Valiev Institute of Physics and Technology of RAS, Yaroslavl, Russia) using standard methods [21,22]. The ion beam diameter was not more than 15-20 µm, the relative error for the majority of elements did not exceed 15%, and the detection limit is 10 ppb on average.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, large olivine crystals are uncommon on the Earth's surface and are restricted to slowly cooled mantle rocks: xenoliths or ophiolites. In basalts, olivine phenocrysts are commonly small (<2 mm in size [15,16]). Notably, unlike other igneous gemminerals (e.g., garnet, tourmaline, beryl), olivine is characterized by low concentrations of most trace elements (well below 1 ppm), which do not fit well its simple crystal structure and chemical composition [17][18][19].…”
Section: Introductionmentioning
confidence: 99%